Study of the serum levels of polyunsaturated fatty acids and the expression of related liver metabolic enzymes in a rat valproate-induced autism model. Issue 44 (August 2015) - Zhao, Gang; Gao, Jingquan; Liang, Shuang; Wang, Xuelai; Sun, Caihong; Xia, Wei; Hao, Yanqiu; Li, Xiang; Cao, Yonggang; Wu, Lijie
Graphical abstract: Highlights: VPA rats had significantly lower serum levels of PUFAs compared to the controls. The expression of PUFAs metabolic enzymes in liver was significantly decreased. Hippocampus neuron injury may be involved in VPA-induced autism model. The VPA-induced autism model has shown sex specific dimorphic effects. Abstract: To investigate whether the decreased level of serum polyunsaturated fatty acids (PUFAs) in patients with autism is associated with the expression of related liver metabolic enzymes, we selected rats that were exposed to valproic acid (VPA) on embryonic day 12.5 (E12.5) as a model of autism. We observed the serum levels of PUFAs and the expression of related liver metabolic enzymes, including Δ5-desaturase, Δ6-desaturase and elongase (Elovl2), in VPA-exposed and control rats on postnatal day 35 (PND35) and conducted sex dimorphic analysis. We found that the levels of serum PUFAs and related liver metabolic enzymes in the VPA rats were significantly reduced, in association with autism-like behavioral changes, the abnormal expression of apoptosis-related proteins and hippocampal neuronal injury, compared to the control rats and showed sex difference in VPA group. This finding indicated that rats exposed to VPA at the embryonic stage may exhibit reduced synthesis of serum PUFAs due to the down-regulation of liver metabolic enzymes, thereby inducing nervous system injury and behavioral changes, which is affected by sex in the meantime.